PENGARUH MODEL KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VII SMP N 8 SAROLANGUN - Anik Santanik (Mat-Edukasia, 2018)
The purpose of this study was to describe mathematical communication skills using a cooperative learning model type two stay two stray better than conventional learning. The study used a quantitative approach with the experimental method. The study population was all students of class VII of SMP N 8 Sarolangun totaling three classes with samples of the VIIA class as the experimental class and VIIB class as the control class. The instruments used are test questions for essay mathematical communication skills. The results of the data analysis requirements show that the data of the two sample classes are normally distributed and have a non-homogeneous variance. Hypothesis testing uses the t-test formula. Based on the results of the analysis of research data shows that tcount is greater than t table or 6.576> 1.729 in the one-party test. Because tcount> t table then Ho is rejected and Ha is accepted, so it can be concluded that mathematical communication skills using cooperative learning models of type two stay two stray are better than conventional learning of class VII students of SMP N 8 Sarolangun. Keywords: cooperative learning model type two stay two stray, conventional, mathematical communication skills.